Semicrystalline Conjugated Polymers with Well‐Defined Active Sites for Nitrogen Fixation in a Seawater Electrolyte. Issue 35 (31st July 2022) - Lai, Feili; Huang, Jiajia; Liao, Xunfan; Zong, Wei; Ge, Lingfeng; Gan, Feng; Fang, Yuting; Miao, Yue‐E; Hofkens, Johan; Liu, Tianxi; Dai, Liming
Abstract: Faradaic efficiency for the nitrogen reduction reaction (NRR) is often limited by low N2 solubility in the electrolyte, while a large number of intimate contacts between the electrolyte and solid catalyst can also inevitably sacrifice many active sites for the NRR. Here, it is reported that a "quasi‐gas–solid" interface formed in donor–acceptor‐based conjugated polymers (CPs) is beneficial to boosting the NRR process and at the same time suppressing the competing hydrogen evolution reaction. Of particular interest, it is found that a semicrystalline CP catalyst, SC‐PBDT‐TT, exhibits a high Faradaic efficiency of up to 60.5% with a maximum NH3 production rate of 16.8 µg h −1 mg −1 in a neutral‐buffered seawater electrolyte. Molecular dynamics and COMSOL Multiphysics simulations reveal the origin of the observed high NRR performance arising from the presence of desirable crystal regions to resist the penetration of H2 O molecules, leading to the formation of a "quasi‐gas–solid" interface inside the catalyst for a favorable direct‐contact between the catalyst and N2 molecules. Furthermore, high‐throughput computations, based on density functional theory, reveal the actual real active site for N2 adsorption and reduction in SC‐PBDT‐TT. This work provides a new framework for optimizing NRR performance of metal‐free catalysts by controlling their crystallinities. Abstract : A "quasi‐gas–solid" interface is well constructed by introducing a suitable semicrystalline structure in donor–acceptor‐based conjugated polymers to significantly boost the nitrogen reduction reaction with a high Faradaic efficiency of 60.5% and a maximum NH3 yield rate of 16.8 µg h −1 mg −1 in a neutral‐buffered seawater electrolyte.